Sex as arche, or is sex change possible according to Aristotle? - Sowa, Joanna (Hybris, 2016)
According to Aristotle’s views presented in his logical works and Metaphysics, sex appears to be an essential attribute of the genus animal, and maleness and femaleness are a pair of contrary qualities, although it is not quite clear what sort of contrariety Aristotle understands the contrariety of sex to be. As qualities admit of variation of degree, and in the case of contraries there are possible changes from one into the other, in this article I address the question if the sex of an individual animal can also be changed into the opposite one. In De generatione animalium Aristotle describes sex as arche — arche of generation, but also arche of every animal’s external appearance and generative ability. Aristotle applies this term to two body parts, which he presents as factors determining sex: the heart as an origin of natural heat, and, above all, the genitals. In the case of males, destruction of the latter, i.e. castration, is depicted as a sex change, because the male becomes like the female in respect of external form and lack of generative power. As change in the other direction is impossible, we can conclude that the contrariety of sex seems to be, according to Aristotle, an opposition of possession and privation.